2002
DOI: 10.1183/09031936.02.00016102
|View full text |Cite
|
Sign up to set email alerts
|

Benefits at 3 yrs of an asthma education programme coupled with regular reinforcement

Abstract: The benefits at 3 yrs of an asthma self-management education programme coupled with educational reinforcement were assessed at follow-up visits in 63 adults with chronic asthma.Changes in asthma-related morbidity parameters, lung function and use of different classes of drugs before intervention and after 1, 2 and 3 yrs of the asthma education programme were compared using Friedman one-way analysis of variance.Improvements in the number of days off work or school, general practitioner consultations, admissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…Many studies have shown that involving patients in the treatment decisions increases their quality of lives (41,42). At the 3rd-month assessment stage of our study, the asthma self-management education improved the quality of lives of asthmatics, especially in the general health and the vitality dimensions of SF-36.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that involving patients in the treatment decisions increases their quality of lives (41,42). At the 3rd-month assessment stage of our study, the asthma self-management education improved the quality of lives of asthmatics, especially in the general health and the vitality dimensions of SF-36.…”
Section: Discussionmentioning
confidence: 99%
“…To be involved in treatment decisions increases the quality of life of asthma patients [2,3]. A recent metaanalysis of studies containing written asthma action plans and standard treatments revealed a 40% decrease in asthmarelated presentation to hospitals and a 20% decrease in emergency visits by patients with an action plan [4].…”
Section: Introductionmentioning
confidence: 99%
“…To help adults with asthma reach this goal, researchers have developed, implemented and evaluated adult asthma education programs. (Brown, Reeves, Meyerson, & Korzeniewski, 2006;Castro et al, 2003;Courturaud et al, 2002;Ignacio-Garcia et al, 2002;Janson et al, 2003;Perneger et al, 2002;Schaffer & Tian, 2004;Schott-Baer, 1999;Smith et al, 2007;Steuten, Vrijhoef, Van Merode, Wesseling, & Spreeuwenberg, 2006;Thoonen et al, 2003;Yilzaz & Akkaya, 2002) Recently, a Cochrane review by Gibson et al (2005) assessed the value of adult asthma self-management interventions. The review assessed the effectiveness of asthma education, self-monitoring, regular medical review, and written action plans.…”
mentioning
confidence: 96%